Relationship between Health Literacy and Self-Care Behaviors in Hypertensive Patients - Majid Barati; Fatemeh Bayat; Zahra Alsadat Asadi; Fatemeh Afshari Moshir; Maryam Afshari (Journal of Education and Community Health)
Aims: Hypertension is one of the most common health problems with significant consequences. Management of hypertension is mainly related to self-care status. Health literacy is one of the factors in accessing information related to health and better self-care. Therefore, the aim of the present study was to determine the relationship between health literacy and self-care behaviors of hypertensive patients referred to health centers. Instrument & Methods: In this descriptive-analytical study, 240 patients with hypertension referred to Hamadan Comprehensive Health Centers in 2019 were selected by multistage random sampling method and entered the study. The data were collected by interview and based on standard questionnaires of Health Literacy for Iranian Adults (HELIA) and self-care questionnaire. Data were analyzed by SPSS 24 software using Pearson correlation tests and linear regression. Findings: 29.2% of patients had inadequate health literacy and 42.1% had moderate self-care. There was a positive significant correlation between all components of health literacy and self-care in patients (p<0.05). The level of education, economic status and self-care had a statistically significant relationship with patients' health literacy (p<0.05). Also, body mass index and health literacy had a statistically significant relationship with self-care (p<0.05). Conclusion: Health literacy is one of the important factors in improving the self-care behaviors of patients with hypertension.